Response of low latitude D-region ionosphere to the total solar eclipse of 22 July 2009 deduced from ELF/VLF analysis - Singh, Ashutosh K.; Singh, Rajesh; Veenadhari, B.; Singh, A. K. (My University, 2012)
Response of the D-region of the ionosphere to the total solar eclipse of 22 July 2009 at low latitude, Varanasi (Geog. lat., 25.27° N; Geog. long., 82.98° E; Geomag. lat. = 14° 55’ N) was investigated using ELF/VLF radio signal. Tweeks, a naturally occurring VLF signal and radio signals from various VLF navigational transmitters are first time used simultaneously to study the effect of total solar eclipse (TSE). Tweeks occurrence is a nighttime phenomena but the obscuration of solar disc during TSE in early morning leads to tweek occurrence. The changes in D-region ionospheric VLF reflection heights (h) and electron density (ne: 22.6–24.6 cm−3) during eclipse have been estimated from tweek analysis. The reflection height increased from ∼89 km from the first occurrence of tweek to about ∼93 km at the totality and then decreased to ∼88 km at the end of the eclipse, suggesting significant increase in tweek reflection height of about 5.5 km during the eclipse. The reflection heights at the time of totality during TSE are found to be less by 2–3 km as compared to the usual nighttime tweek reflection heights. This is due to partial nighttime condition created by TSE. A significant increase of 3 dB in the strength of the amplitude of VLF signal of 22.2 kHz transmitted from JJI-Japan is observed around the time of the total solar eclipse (TSE) as compared to a normal day. The modeled electron density height profile of the lower ionosphere depicts linear variation in the electron density with respect to solar radiation as observed by tweek analysis also. These low latitude ionospheric perturbations on the eclipse day are discussed and compared with other normal days.
Keywords: Total solar eclipse; D-region of Ionosphere; ELF-VLF waves; Tweeks